Study of the Role of Casein Kinase I epsilon in Breast Cancer Using Drosophila as a Model - Matulová, Jana (Jihočeská univerzita, 2009)
A particular allele of the Drosophila discs overgrown locus called dco3 leads to hyperplastic overgrowth of imaginal wing discs. Since high rate of mutations in human homologue of the dco gene coding Casein kinase I epsilon was found in breast cancer tissue samples, I attempted to recreate the observed mutations in the Drosophila genome.
Study of the Role of Casein Kinase I epsilon in Breast Cancer Using Drosophila as a Model